Model Pengendalian Banjir Terpadu Dengan Manajemen Hulu-Tengah-Hilir Di Propinsi Lampung: Studi Kasus Way Bulok Kabupaten Pringsewu - Anwar; Agustinus Purna Irawan; Endro Prasetyo Wahono (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Borneo Tarakan, 2025)
This study aims to develop an integrated flood control model in the Way Bulok watershed, Pringsewu Regency, Lampung. Using the HEC-RAS application, a design flood discharge analysis was carried out to evaluate the potential for flooding based on maximum daily rainfall data from 2014 to 2024. The methods used include dispersion analysis, distribution suitability test, and design rainfall calculation using the Log Pearson III method. The results show that the design flood discharge value increases with increasing recurrence period, ranging from 25.17 m³/second to 123.76 m³/second. Inundation modeling at three focal points (upstream, middle, and downstream) shows no inundation at the two and 5-year return periods, while at the 10-year return period, one point experiences a maximum value without inundation. At the 25 year return period, two points experience inundation. This study concludes that the HEC-RAS model effectively predicts and controls flood potential in the Way Bulok Watershed, providing a strong basis for better water resource management and disaster mitigation strategies in the region.